2004
DOI: 10.1111/j.1559-1816.2004.tb02547.x
|View full text |Cite
|
Sign up to set email alerts
|

The Persuasiveness of Source Credibility: A Critical Review of Five Decades' Evidence

Abstract: This paper reviews the empirical evidence of the effect of credibility of the message source on persuasion over a span of 5 decades, primarily to come up with recommendations for practitioners as to when to use a high-or a low-credibility source and secondarily to identify areas for future research. The main effect studies of source credibility on persuasion seem to indicate the superiority of a high-credibility source over a low-credibility one. Interaction effect studies, however, show source credibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
1,202
4
22

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,601 publications
(1,280 citation statements)
references
References 135 publications
52
1,202
4
22
Order By: Relevance
“…Extending this previous research, we further found that time spent receiving word-of-mouth explained incremental variance in perceived attractiveness and actual application decisions beyond potential applicants' exposure to recruitment adver- Step 1 Step 2 Step 1 Step tising, the recruitment website, recruitment events, and publicity. This further corroborates the accessibility-diagnosticity model, which posits that word-of-mouth's unique characteristics as a company-independent experiential recruitment source increase its accessibility and diagnosticity, allowing it to influence potential applicants' perceptions and decisions beyond company-dependent and informational sources (Bone, 1995;Cable & Turban, 2001;Herr et al, 1991;Pornpitakpan, 2004). Whereas the current field study found that time spent receiving negative word-of-mouth early in the recruitment process did not significantly predict potential applicants' perceived organizational attractiveness and application decisions, Van Hoye and Lievens (2007) observed a large negative impact on students' perceptions of organizational attractiveness in their lab study.…”
Section: Main Conclusionsupporting
confidence: 74%
See 1 more Smart Citation
“…Extending this previous research, we further found that time spent receiving word-of-mouth explained incremental variance in perceived attractiveness and actual application decisions beyond potential applicants' exposure to recruitment adver- Step 1 Step 2 Step 1 Step tising, the recruitment website, recruitment events, and publicity. This further corroborates the accessibility-diagnosticity model, which posits that word-of-mouth's unique characteristics as a company-independent experiential recruitment source increase its accessibility and diagnosticity, allowing it to influence potential applicants' perceptions and decisions beyond company-dependent and informational sources (Bone, 1995;Cable & Turban, 2001;Herr et al, 1991;Pornpitakpan, 2004). Whereas the current field study found that time spent receiving negative word-of-mouth early in the recruitment process did not significantly predict potential applicants' perceived organizational attractiveness and application decisions, Van Hoye and Lievens (2007) observed a large negative impact on students' perceptions of organizational attractiveness in their lab study.…”
Section: Main Conclusionsupporting
confidence: 74%
“…According to the accessibility-diagnosticity model, company-independent sources such as word-of-mouth are more credible and therefore more diagnostic than company-dependent sources such as advertising (Pornpitakpan, 2004;Van Hoye & Lievens, 2007). In addition, the framework suggests that personal sources such as word-of-mouth are more accessible than impersonal sources such as mass media publicity (Herr et al, 1991;Van Hoye & Lievens, 2005).…”
Section: Outcomes Of Word-of-mouth As a Recruitment Sourcementioning
confidence: 99%
“…A multitude of source features affect message acceptance (Hovland et al 1953;Pornpitakpan 2004). If a source is perceived as expert and trustworthy, resistance to its message is reduced and the likelihood of acceptance increases (Tormala and Petty 2004).…”
Section: Malleability Of Inhalant Relevant Spesmentioning
confidence: 99%
“…Indeed, as Leding (2012) noted, whereas persuasion tactics are not necessary to cause memory distortions or 'false memories', they do invariably seem to make such distortions more likely to happen. Both attitudes and memories, for instance, are changed more readily by credible messengers than by non-credible messengers (Dodd & Bradshaw, 1980;French, Garry, & Mori, 2011;Hovland & Weiss, 1951;Pornpitakpan, 2004), yet these effects diminish over time as memory for the message becomes stronger than memory for its 5 source (Hovland & Weiss, 1951;Underwood & Pezdek, 1998). Both attitudes and memories are often bolstered against change when a warning is provided in advance of an attempt to influence (Gallo, Roberts, & Seamon, 1997;Landau & von Glahn, 2004;Petty & Cacioppo, 1977), but are typically less so when the warning is instead provided afterwards (Gerrie & Garry, 2011;Greene, Flynn, & Loftus, 1982;Kiesler & Kiesler, 1964).…”
Section: A Tale Of Two Literaturesmentioning
confidence: 99%